The Association of School Nurse Workload With Student Health and Academic Outcomes: A Cross-Sectional Study. - Schroeder, Krista; Young, Ally; Adman, Gail; Ashmeade, Ann Marie; Bonas, Estherlyn; Day, Sophia E.; Konty, Kevin (Journal of School Nursing, 2023)
This study assessed associations between school nurse workload and student health and academic outcomes. We hypothesized that lower school nurse workload would be associated with better student outcomes, with associations being greater for members of groups who experience health disparities. Our methods entailed secondary analysis of data for New York City school students in kindergarten through 12th grade during 2015–2016 (N = 1,080,923), using multilevel multivariate regression as the analytic approach. Results demonstrated lower school nurse workload was associated with better outcomes for student participation in asthma education but not chronic absenteeism, early dismissals, health office visits, immunization compliance, academic achievement, or overweight/obesity. Our findings suggest school nurses may influence proximal outcomes, such as participation in disease-related education, more easily than downstream outcomes, such as absenteeism or obesity. While contrary to our hypotheses, results align with the fact that school nurses deliver community-based, population health–focused care that is inherently complex, multilevel, and directly impacted by social determinants of health. Future research should explore school nurses' perspectives on what factors influence their workload and how they can best impact student outcomes.